Cultivo do girassol submetido a doses de biofertilizante caprino e lâminas de irrigação na região do Maciço de Baturité - Borges, Francisca Robevania Medeiros (2017)
Sunflower cultivation has economic importance attributed mainly to the presence of oil in its seeds, which can be limited by low water availability and inadequate fertilization. This study aimed to cultivate the sunflower under organic fertilization under doses of goat biofertilizer and irrigation slides, based on percentage of evaporation of Class "A" tank, in two consecutive crop cycles. The research was conducted at the Experimental Farm Piroás, belonging to the University of International Integration of Afro-Brazilian Lusophony - UNILAB, in the municipality of Redenção, Ceará. The experimental design was a randomized complete block design, with sub-divided plots in which the plots consisted of two cultivation cycles, the subplots for five doses of goiter biofertilizer (0, 300, 600, 900 and 1,200 mL plant-1 week-1) applied via the irrigation system and the sub-sub-plots for five irrigation blades (33, 66, 100, 133 and 166% of the evaporation measured in Class "A" tank). Growth characteristics (plant height, stem diameter, shoot dry matter, root dry matter and internal diameter of the shoot) were evaluated, production characteristics (yield and weight of 1,000 achenes), post-harvest characteristics (oil content and yield, protein content and yield), as well as soil chemical characteristics, plant material analysis and water use efficiency in the production of achenes. The soil nutrient contents presented the highest values in the 1st cycle of cultivation, with the exception of Ca and Mg, and respond strongly to the application of the gofer biofertilizer, being more effective in the higher doses. The leaf contents were adequate to the recommended range for the crop only in the 1st cycle, except in Na and Ca. Doses between 900 and 1,000 mL plant- 1 week-1 and leaf above 120% of ACE are indicated to provide greater plant growth of sunflower. The highest productivity was obtained in the 1st cycle with a value of 1,220.78 kg ha-1. Biofertilizer doses between 800 and 1200 mL plant-1 week-1 associated with irrigation slides in the range of 120 to 166% of ACE provided positive responses in production and post-harvest variables in the first cycle. Already in the 2nd cycle, the association between doses between 1,000 and 1,200 mL plant-1 week-1 and irrigation depth between 140 and 166% of ACE showed better results. The application of the goat biofertilizer does not alter the sunflower oil content, however, there is evidence of increases for this variable in response to the irrigation slides, with maximization of the values indicated in the slides of 409.42 and 843 mm for the 1st and 2nd cycles, respectively. The oil content presented similar values between the cultivation cycles (48%). Protein levels were higher in the second crop cycle (14%), effectively responding to the combination of the mean 100% ECA leaf with the 536 mL plant-1 week-1 dose of goiter liquid fertilizer.